Variability of performance status assessment between patients with hematologic malignancies and their physicians. Issue 3 (4th March 2018) - Leal, Alexis D.; Allmer, Cristine; Maurer, Matthew J.; Shanafelt, Tait D.; Cerhan, James R.; Link, Brian K.; Thompson, Carrie A.
Abstract: This study was conducted to determine the incidence of inter-observer variability in Eastern Cooperative Oncology Group (ECOG) performance status (PS) rating between patients with leukemia and lymphoma and their physicians. ECOG PS was assessed at diagnosis by patients and their physicians and stratified by disease subtype, gender, age, disease stage and education. Association between patient- and physician-rated PS and overall survival (OS) was stratified by subtype and prognostic risk score. Overall, 65% of patients and physicians rated PS the same. Age, disease stage and disease subtype were significant predictors of PS disagreement. PS was a significant predictor of OS irrespective of assessment by patients or physicians across all subtypes except those with Hodgkin lymphoma. These findings suggest the need for physicians to better communicate with patients when determining PS, as PS is a strong predictor of survival and is critical in treatment decisions, including determining fitness for cancer treatment.